2018
DOI: 10.1038/s41419-018-0692-9
|View full text |Cite
|
Sign up to set email alerts
|

The hedgehog and Wnt/β-catenin system machinery mediate myofibroblast differentiation of LR-MSCs in pulmonary fibrogenesis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive and fatal lung disease that is characterized by enhanced changes in stem cell differentiation and fibroblast proliferation. Resident mesenchymal stem cells (LR-MSCs) can undergo phenotype conversion to myofibroblasts to augment extracellular matrix production, impairing function and contributing to pulmonary fibrosis. Hedgehog and Wnt signaling are developmental signal cascades that play an essential role in regulating embryogenesis and tissue homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 56 publications
2
44
0
1
Order By: Relevance
“…For example, GLI could bind to promoter of Wnt genes to regulate Wnt/β-catenin signaling [41], and β-catenin could enhance GLI1 transcriptional activity [42]. Recently, crosstalk between Wnt and Hh was shown to be involved in pulmonary fibrosis, and GLI1 was proved to be a potential therapeutic target in pulmonary fibrosis [43]. The present study showed that GLI1 expression was promoted by Wnt activation in LF, and additional knockdown of PRC1 could inhibit GLI1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GLI could bind to promoter of Wnt genes to regulate Wnt/β-catenin signaling [41], and β-catenin could enhance GLI1 transcriptional activity [42]. Recently, crosstalk between Wnt and Hh was shown to be involved in pulmonary fibrosis, and GLI1 was proved to be a potential therapeutic target in pulmonary fibrosis [43]. The present study showed that GLI1 expression was promoted by Wnt activation in LF, and additional knockdown of PRC1 could inhibit GLI1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggest that MSC-sourced CM and Exos may represent a compelling alternative to MSCs in the treatment of ALF and liver fibrosis (Table 1) [13,14,15,16,17,18,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88].…”
Section: Experimental Evidence For Therapeutic Potential Of Msc-dementioning
confidence: 99%
“…Beneficial effects of MSC-CM and MSC-Exo-based therapy have been demonstrated in the animal models of ALI, asthma, COPD and IPF (Table 2) [19,20,21,22,83,84,85,86,87,88,89,90,91]. Importantly, MSC-CM and MSC-EVs managed to induce regeneration of injured epithelium, attenuation of inflammation and fibrosis in the lungs in similar manner as transplanted MSCs [19,24,84,85,86,87].…”
Section: Experimental Evidence For Therapeutic Potential Of Msc-dementioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, despite the fact that MSCs can be used for the attenuation of chronic lung inflammation and fibrosis, plenty of evidence suggests that aberrant activation of Wnt/ β -catenin and TGF- β signaling pathways in lung-resident MSCs might induce their differentiation towards myofibroblasts and could, consequently, contribute to the development of IPF [104]. In line with these findings, a pharmacological inhibitor of Wnt/ β -catenin signaling (ICG-001) managed to prevent MSC-myofibroblst transition and protected from bleomycin-induced fibrosis [105].…”
Section: Msc-based Therapy Of Ipfmentioning
confidence: 99%